2013
DOI: 10.1007/s00138-013-0570-5
|View full text |Cite
|
Sign up to set email alerts
|

Thermal cameras and applications: a survey

Abstract: Thermal cameras are passive sensors that capture the infrared radiation emitted by all objects with a temperature above absolute zero. This type of camera was originally developed as a surveillance and night vision tool for the military, but recently the price has dropped, significantly opening up a broader field of applications. Deploying this type of sensor in vision systems eliminates the illumination problems of normal greyscale and RGB cameras.This survey provides an overview of the current applications o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
292
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 585 publications
(298 citation statements)
references
References 162 publications
(69 reference statements)
0
292
0
6
Order By: Relevance
“…IR thermal cameras are one of the sensing technologies utilized in laser welding applications to capture the temperature distribution to the welded component. Thermal cameras are passive sensors that imprint the infrared radiation, emitted by all objects with a temperature above absolute zero [24]. Today, the thermal imaging monitoring systems, as it is mentioned in [25], are more and more implemented into industry, due to the fact that they offer many advantages over other techniques used for detection of the weld pool temperature.…”
Section: Thermalmentioning
confidence: 99%
“…IR thermal cameras are one of the sensing technologies utilized in laser welding applications to capture the temperature distribution to the welded component. Thermal cameras are passive sensors that imprint the infrared radiation, emitted by all objects with a temperature above absolute zero [24]. Today, the thermal imaging monitoring systems, as it is mentioned in [25], are more and more implemented into industry, due to the fact that they offer many advantages over other techniques used for detection of the weld pool temperature.…”
Section: Thermalmentioning
confidence: 99%
“…Thermal radiation is emitted by objects with a temperature higher than absolute zero (-273 °C/0 K). The infrared radiation region is between visible light and microwaves within the wavelength spectrum of 0.78 -1000 μm [16,17]. …”
Section: Infrared Thermographymentioning
confidence: 99%
“…However, features are sparse in thermal images, and it might thus be more difficult to determine identities or distinguish between objects. An extensive review of thermal cameras in computer vision is found in [24]. When combined, RGB and thermal cameras extend the visibility of the road users and improves the robustness of traffic surveillance algorithms.…”
Section: Thermal-visible Intersection Data Setmentioning
confidence: 99%